Perancangan Kampanye Cara Pintar dalam Berhemat Listrik Prabayar - Setyo, Sutikno Try; Iswandi, Heri; Yulius, Yosef (UNIVERSITAS INDO GLOBAL MANDIRI)
Government innovation by presenting prepaid electricity services or better known as